Pathogenicity of fungal isolates (Ascomycota: Hypocreales) against Peregrinus maidis, Delphacodes kuscheli (Hemiptera: Delphacidae), and Dalbulus maidis (Hemiptera: Cicadellidae), vectors of corn diseases - Toledo, Andrea Vanesa (2007)
Preliminary screening assays were carried out on 17 isolates from five fungal species Beauveria bassiana, Lecanicillium muscarium, Metarhizium anisopliae, Isaria farinosa, and I. fumosorosea. The three most effective isolates against Peregrinus maidis (Hemiptera: Delphacidae) were B. bassiana CEP 147, CEP 150, and CEP 189. There were no consistent differences found in males and females regarding fungal susceptibility. However, more females than males were proportionally infected. There was not a correlation between the percentage of conidial germination and the percentage of mortality caused by fungal infection in any of the treatments. Only B. bassiana CEP 147, which caused a cumulative mortality of 69.8 ± 6.4% after 7 days post-inoculation, was selected to be assayed against adults of P. maidis, Delphacodes kuscheli (Hemiptera: Delphacidae), and Dalbulus maidis (Hemiptera: Cicadellidae). In pathogenicity tests significant differences were observed among treatments. After 2 weeks post-inoculation, both D. kuscheli (cumulative mortality of 73.3 ± 9.0%) and P. maidis (cumulative mortality of 68.6 ± 6.7%) were significantly more susceptible than D. maidis (cumulative mortality of 49.9 ± 9.7%) to the selected isolate.